Human microbiota modulation via QseC sensor kinase mediated in the Escherichia coli O104:H4 outbreak strain infection in microbiome model - Machado Ribeiro, Tamara Renata [UNESP]; Salgaço, Mateus Kawata [UNESP]; Adorno, Maria Angela Tallarico; da Silva, Miriam Aparecida; Piazza, Roxane Maria Fontes; Sivieri, Katia [UNESP]; Moreira, Cristiano Gallina [UNESP] (Springer Nature, 2021)
Background: The intestinal microbiota plays a crucial role in human health, adjusting its composition and the microbial metabolites protects the gut against invading microorganisms. Enteroaggregative E. coli (EAEC) is an important diarrheagenic pathogen, which may cause acute or persistent diarrhea (≥14 days). The outbreak strain has the potent Shiga toxin, forms a dense biofilm and communicate via QseBC two-component system regulating the expression of many important virulence factors. Results: Herein, we investigated the QseC histidine sensor kinase role in the microbiota shift during O104:H4 C227–11 infection in the colonic model SHIME® (Simulator of the Human Intestinal Microbial Ecosystem) and in vivo mice model. The microbiota imbalance caused by C227–11 infection affected ỿ-Proteobacteria and Lactobacillus spp. predominance, with direct alteration in intestinal metabolites driven by microbiota change, such as Short-chain fatty acids (SCFA). However, in the absence of QseC sensor kinase, the microbiota recovery was delayed on day 3 p.i., with change in the intestinal production of SCFA, like an increase in acetate production. The higher predominance of Lactobacillus spp. in the microbiota and significant augmented qseC gene expression levels were also observed during C227–11 mice infection upon intestinal depletion. Novel insights during pathogenic bacteria infection with the intestinal microbiota were observed. The QseC kinase sensor seems to have a role in the microbiota shift during the infectious process by Shiga toxin-producing EAEC C227–11. Conclusions: The QseC role in C227–11 infection helps to unravel the intestine microbiota modulation and its metabolites during SHIME® and in vivo models, besides they contribute to elucidate bacterial intestinal pathogenesis and the microbiota relationships.
Keywords: EAEC; Microbiota; QseC; SHIME®